Meta-analysis: clinical features and treatments of lung cancer in combined pulmonary fibrosis and emphysema - Zhou, Jiayu; Jiang, Yu (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: There are many epidemiological pieces of evidence that show combined pulmonary fibrosis and emphysema (CPFE) patients have an increased risk of lung cancer. We conducted a systematic review of all published data to define the characteristics and treatments of lung cancer that develops in CPFE by performing a meta-analysis.Methods: Databases(including PubMed, Medline, CNKI, VIP, etc.) were searched to find original articles that related to lung cancer in CPFE(CPFE-LC) patients and a meta-analysis was used to analyze the included 15 articles. Stata17.0 software was performed for this meta-analysis.Results: Fifteen original studies that assessed 5933 patients were included in this meta-analysis. In the pooled data, people with CPFE-LC were elderly(70.58 years) and heavy smokers( 0.959, 45.793 pack-years), with a male predominance(0.959). Most lung cancer in CPFE was located in the lower lobe(0.533) and obvious areas of pulmonary fibrosis(0.516). Highest prevalence of cellular subtypes of lung cancer in CPFE was squamous carcinoma(SQCC, 0.437) and chemotherapy was the main treatment(0.387). The mortality rate was 0.720(95%CI: 0.657-0.783) and the 5-year survival rate was 0.250(95%CI: 0.133-0.368). The main cause of death was infection(0.268) and respiratory failure was the main cause of death after surgery(0.392).Conclusions: Lung cancer in CPFE, most commonly SQCC, presents in elderly heavy smokers with a male, located in the lower lobe of the lung and the areas of fibrosis predominance. Chemotherapy is the main treatment and the optimal treatment remains to be explored.